PUSHOVER ANALYSIS OF THE STRUCTURE A 10 FLOOR BUILDING WITH ATC-40 - Dermawan Zebua; Koespiadi Koespiadi (NAROTAMA UNIVERSITY, Indonesia, 2022)
The concept of earthquake-resistant buildings is very meaningful to try on buildings located in certain earthquake areas, especially in Indonesia considering the situation which is located in a shock area with a fairly high intensity of events. The purpose of this research is to determine the seismic performance criteria of the planned structure using the SMRF (Special Moment Resisting Frame) structural system from the results of the displacement values using the ATC-40 code, showing the yielding scheme (plastic joint distribution) that occurs from the calculation results of the software program, knowing the pattern of building collapse so that it can be known joint- joint that is damaged and damaged from the pushover analysis. From the results of the research, the building structure is able to provide nonlinear behavior which is indicated by the initial phase and the majority of the occurrence of plastic joints occurs in new beam elements and then column elements and has fulfilled the earthquake-resistant building concept, namely strong column - weak beam. The results of the structural performance evaluation according to the ATC-40 rule that the Performance Level of the SMRF building in the x and y directions is at a Performance Level of 0.011 in the Immediate Occupancy (IO) category where the building is safe during an earthquake, the risk of loss of life and structural failure is not too significant, the building does not experience significant damage, and can be reused and not disturbed by repair problems, where the strength and stiffness are approximately the same as the conditions before the earthquake.